Evaluating frequency regulation operated on two stationary energy systems with batteries from electric vehicles. (November 2018) - Bauer, Michaela; Nguyen, Tam T.; Jossen, Andreas; Lygeros, John
Abstract: Two medium-sized stationary energy storage systems of 55 kW and 120 kW, built from repurposed BMW i3 batteries, comprise the basis of this study. Giving a supplementary overview of applications for lithium-ion based energy storage systems, this paper focuses on the operational behaviour of the two systems for a frequency regulation application. A new analysis method for assessing system and battery pack behaviour is presented. Then the two topologies are assessed in terms of their characteristics for load profile, load response, current, state of charge, temperature and system performance. The systems differ both in their type of housing, which influences cell temperature, and system architecture, which affects system performance. Sophisticated cooling, recharging, and power distribution strategies are found to be necessary to ensure system reliability and are essential for optimisation. We conclude with a discussion on strategies to attain maximum system performance and minimum battery cell degradation.